Children learning outside the classroom : from birth to eleven - Waite, Sue, ....- (Thousand Oaks (Cal.) : SAGE Pub., 2017)
The new edition of this bestselling textbook continues to help students and professionals understand the importance of getting children learning outside the traditional classroom, and is packed full of creative information and ideas for teachers and practitioners to incorporate outdoor activities throughout the school curriculum. Significantly revised and updated the second edition now includes 7 brand new chapters on: Methods of assessment and evaluation Global perspectives on outdoor learning Developing whole school approaches to indoor and outdoor teaching Technology and its role outside the classroom Special Education Needs and Disabilities (SEND) and learning outdoors Forest School The environmental sector and outdoor learning Whether you're training to become a teacher, or already working in the classroom, this book demonstrates how the outdoor environment is enriching learning opportunities for children and deepening their connections with the natural world. NOW FEATURING! Online resources that include free SAGE journal articles, weblinks, annotated further readings and video to help translate theory into real life practice. Sue Waite will be discussing key ideas from Children Learning Outside the Classroom: From Birth to Eleven in the SAGE Early Years Masterclass, a free professional development experience hosted by Kathy Brodie. To sign up, or for more information.
Keywords: Buitenlessen; Outside learning; Schoolorganisatie